Ingestion of oxygenated water enhances lactate clearance kinetics in trained runners - Neil Fleming; Jeremiah Vaughan; Matthew Feeback (Taylor & Francis Group, 2017)
Background Drinks with higher dissolved oxygen concentrations have in recent times gained popularity as a potential ergogenic aid, despite a lack of evidence regarding their efficacy. The aim of this study was to assess effects of ingestion of an oxygen supplement (OS) on exercise performance and post-exercise recovery in a group of trained runners. Methods Trained male runners (n = 25, mean ± SD; age 23 ± 6 years, mass 70 ± 9 kg, BMI 21.9 ± 2.7 kg.m−2 VO2max 64 ± 6mL.kg−1.min−1), completed a randomised double blinded, crossover study to assess the effect of ingestion of OS solution on exercise performance and recovery. Trials consisted of a 30min rest period, 5min warm-up, a 5000m treadmill time-trial, and a 30min passive recovery. Participants ingested 6x15mL of either OS or a taste matched placebo during the trials (3 during the rest phase, 1 during exercise and 2 during the recovery). Muscle tissue O2 saturation was measured via near infrared spectroscopy. Blood lactate concentrations were measured prior to, mid-way and directly after the finish of the 5000m time trials and every 3-min during the post-exercise recovery. Results Ingestion of OS did not improve exercise performance. No significant differences were observed for muscle tissue O2 saturation at any time-points. However, lactate clearance was significantly improved during recovery in the OS trials. Both AUC (109 ± 32 vs. 123 ± 38 mmol.min, P < 0.05, d = 0.40) and lactate half-life (λ) (1127 ± 272 vs. 1223 ± 334 s, P < 0.05, d = 0.32) were significantly reduced. Conclusions Despite no evidence of improved exercise performance, ingestion of OS did enhance post-exercise recovery via increased lactate clearance.